A Survey of Requirements Engineering and Software Testing Practices in Agile Teams - Coutinho, Jarbele; Andrade, Wilkerson; Machado, Patrícia (Anais do Simpósio Brasileiro de Testes de Software Sistemático e Automatizado (SAST), 2022)
In agile methods, the priority of fast delivery of operational software has directly reached the execution of the activities foreseen in the Requirements Engineering (RE) and Software Testing (ST) stages. Thus, understanding how these activities have been performed in agile teams and how they can contribute in a coordinated way to the quality of the software developed, appears as a need for both academia and industry. For this, we conducted an unsupervised exploratory research (Survey) with seventy-two professionals who work in the software industry and who have experience with RE and ST activities. In a complementary way, we compared the findings of the Survey with the results already found in the literature and with agile practices. Such findings highlight that: (i) the activities of Agile RE and Agile ST still need to be matured in terms of their implementation in a coordinated way in the projects; (ii) there are some similarities and differences between what has been investigated in academia and the real practices and challenges of the industry; (iii) some agile practices, specific to RE and ST have been used, as well as other agile practices more related to processes, approaches, and software development. Such practices act in a complementary manner.